Mycobacterium smegmatis Bacteria Expressing Mycobacterium tuberculosis-Specific Rv1954A Induce Macrophage Activation and Modulate the Immune Response - Arora, Simran Kaur; Naqvi, Nilofer; Alam, Anwar; Ahmad, Javeed; Alsati, Basma Saud; Sheikh, Javaid Ahmad; Kumar, Prabin; Mitra, Dipendra Kumar; Rahman, Syed Asad; Hasnain, Seyed Ehtesham; Ehtesham, Nasreen Zafar (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (M. tb), the intracellular pathogen causing tuberculosis, has developed mechanisms that endow infectivity and allow it to modulate host immune response for its survival. Genomic and proteomic analyses of non-pathogenic and pathogenic mycobacteria showed presence of genes and proteins that are specific to M. tb. In silico studies predicted that M.tb Rv1954A is a hypothetical secretory protein that exhibits intrinsically disordered regions and possess B cell/T cell epitopes. Treatment of macrophages with Rv1954A led to TLR4-mediated activation with concomitant increase in secretion of pro-inflammatory cytokines, IL-12 and TNF-α. In vitro studies showed that rRv1954A protein or Rv1954A knock-in M. smegmatis (Ms_Rv1954A) activates macrophages by enhancing the expression of CD80 and CD86. An upregulation in the expression of CD40 and MHC I/II was noted in the presence of Rv1954A, pointing to its role in enhancing the association of APCs with T cells and in the modulation of antigen presentation, respectively. Ms_Rv1954A showed increased infectivity, induction of ROS and RNS, and apoptosis in RAW264.7 macrophage cells. Rv1954A imparted protection against oxidative and nitrosative stress, thereby enhancing the survival of Ms_Rv1954A inside macrophages. Mice immunized with Ms_Rv1954A showed that splenomegaly and primed splenocytes restimulated with Rv1954A elicited a Th1 response. Infection of Ms_Rv1954A in mice through intratracheal instillation leads to enhanced infiltration of lymphocytes in the lungs without formation of granuloma. While Rv1954A is immunogenic, it did not cause adverse pathology. Purified Rv1954A or Rv1954A knock-in M. smegmatis (Ms_Rv1954A) elicited a nearly two-fold higher titer of IgG response in mice, and PTB patients possess a higher IgG titer against Rv1954A, also pointing to its utility as a diagnostic marker for TB. The observed modulation of innate and adaptive immunity renders Rv1954A a vital protein in the pathophysiology of this pathogen.